Uremic stomatitis - Ramachandran Sudarshan; Rajeshwari G Annigeri; G P Mamatha; G Sree Vijayabala (Wolters Kluwer Medknow Publications, 2012)
Uremic stomatitis is a rare mucosal disorder associated with renal disorders. Here, we report a case of a 42-year-old male patient suffering from diabetes, angina pectoris, with white curdly pseudomembrane over the dorsal surface of the tongue, which was diffuse. The etiology, clinical features, and treatment are discussed.